Japan's Security Restoration: Evolution, Challenges, and Future Directions - Badawi Habib (2024)
This study examines Japan's security policy evolution from post-World War II pacifism to its current assertive stance, analyzing historical context, key drivers, and challenges. It focuses on shifts under Prime Minister Shinzo Abe, exploring implications for regional stability and international relations, including the U.S.-Japan alliance and emerging security threats.